Stereoscopic Depth Contrast in a 3D Müller–Lyer Configuration: Evidence for Local Normalization. (July 2017) - Harada, Shinya; Mitsudo, Hiroyuki
Depth contrast is a stereoscopic visual phenomenon in which the slant of an element is affected by that of adjacent elements. Normalization has been proposed to be a possible cause of depth contrast, but it is still unclear how depth contrast involves normalization. To address this issue, we devised stereograms consisting of a vertical test line accompanied by several inducer lines, like a three-dimensional variation of the well-known Müller–Lyer configuration. The inducer lines had horizontal binocular disparities that defined a stereoscopic slant about a horizontal axis with respect to the endpoints of the test line. The observer's task was to adjust the slant of the test line about a horizontal axis until it appeared subjectively vertical. The results of two psychophysical experiments found that slant settings were affected by the slant of local inducers, but not by the overall slant of the whole stimulus. These results suggest that, at least for line patterns, the stereo system normalizes depth locally.